WORK-LIFE BALANCE: A PERSPECTIVE OF MULTINATIONAL CORPORATION (MNCs) EMPLOYEE - N. Yolan Pradita; Rosaly Franksiska (Jurnal Bisnis dan Manajemen, 2020)
For a company knowing the work life balance of their employee is a proper way to control the employee performance for company’s development. This study on Work-life balance (WLB) is aimed to help both company and employees manage their family responsibilities, create flexible-work conditions and enable them to perform better particularly in Multinational Company (MNC). This research put forward on the four dimensions of Work life balance from the employee perspective in MNC. The four dimensions include Work Interference with Personal Life (WIPL), Personal Life Interference with Work (PLIW), Personal Life Enhancement of Work (PLEW) and Work Enhancement of Personal Life (WEPL). Deep analyzing on the employee characteristic using a descriptive quantitavive method is also conducted to the measurement of the work life balance to 100 employees in PT. NK. The interesting finding is found during the study whereby in PT. NK as a MNC most of the employees are in a moderate range of WLB and been measure by the cross tabulation with the employee characteristic. The other finding indicated that work life balance is an important aspect which supposed to be notice by a company for all of the employee particularly in a multinational company.